BATASAN USIA KANDUNGAN ANAK SAH TERHADAP WALI NASAB: pandangan masyarakat muslim desa pundong kecamatan diwek kabupaten jombang) - Hari mulyanto, Ana maulida sabila (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2024)
This research aims to find out the review of Islamic law in determining the limitation of gestational age on the status of children and nasab guardians.  The author collects data on how religious leaders resolve the issue of the status of the child's nasab from the nasab guardian in Pundong village. This research is a qualitative field research with a juridical sociological approach. Data collection techniques are interview, observation, and documentation. The author uses descriptive data analysis techniques. This study concludes that the settlement of the nasab status of children from nasab guardians in the community of Pundong Village, Diwek Subdistrict, Jombang Regency follows the rules made by the state, namely including the child's nasab to the father of his mother's legal marriage. The logical law that is built is that state regulations do not mention the limits of gestational age for determining the status of legal children